Synthesis of 18fluoride-fluorodeoxyglucose and its clinical applications in positron emission tomography/computed tomography - Rajeev Kumar; Madhavi Tripathi; Aditi Khurana; Arunav Kumar; Shubha G. Ravindra; Sumit Garg; Manish Kumar; Sanjay Kumar Suman (Wolters Kluwer -Medknow Publications, 2022)
This review article covers a brief explanation on synthesis of Flourodeoxyglucose (18F-FDG) and its clinical uses with emphasis on practical uses. In present scenario, 18F-FDG is the most successful PET radiopharmaceutical because of its half-life and mode of uptake. 18F-FDG synthesised by electrophilic fluorination and Nucleophilic fluorination reaction (preferable Nucleophilic fluorination reaction). The simplicity in synthesis and clinical utility of 18F-FDG, together with its approval by the US FDA and the availability of PET radiopharmaceuticals are probably the main reasons for the flourish of clinical PET. Positron Emission Tomography (PET) has increased the accuracy of metabolic mapping of numerous malignancies, with significant impact on the management of cancer patients for initial staging, restaging and therapy monitoring. PET can provide functional information in addition to morphology from conventional imaging modalities. 18F-FDG is the most commonly used PET tracer and FDG PET can demonstrate the activity of glucose metabolism throughout the entire body in a single session. We describe the clinical utility of FDG in PET and display images of normal distribution and of patients.